Cognitive Level Mapping of Indonesian Arabic Olympiad Questions: A Bloom's Taxonomy Analysis - Muhammad Khozinul Asror; Hosita Laili Rahma; Hasan Syukur; Hanik Mahliatussikah (UIN Raden Mas Said Surakarta, 2026)
Competency-based assessment requires test items capable of measuring higher-order thinking skills; however, the cognitive quality of test items in academic competitions, particularly the Arabic Language Olympiad, has not yet been sufficiently explored empirically. This study aims to examine the distribution of cognitive levels of questions in the 2023 National Arabic Language Olympiad for Madrasah Aliyah based on Bloom’s Revised Taxonomy. This study employs a qualitative approach using content analysis on 100 multiple-choice items. Data collection was conducted through documentation of the official competition questions; subsequently, each question item was analyzed and classified into the six cognitive levels of the Revised Bloom’s Taxonomy, ranging from remembering, understanding, applying, analyzing, evaluating, to creating, by two coders to ensure the reliability of the analysis results. The results of the study show that 53% of the questions fall into the Lower Order Thinking Skills (LOTS) category, which includes C1–C3, while 47% fall into the Higher Order Thinking Skills (HOTS) category, which includes C4–C6; thus, the questions are still dominated by lower-order thinking skills. This finding implies the need to increase the proportion of HOTS questions in the design of the Arabic Language Olympiad’s competitive assessment to foster participants’ critical and analytical thinking skills. This study recommends that test developers pay attention to the balance of cognitive distribution and use the Revised Bloom’s Taxonomy as a standard reference in the development of competition questions at the national level.